Changes in body mass index and clinical outcomes after initiation of contemporary antiretroviral regimens. (1st December 2022) - Bannister, Wendy P.; Mast, T. Christopher; de Wit, Stéphane; Gerstoft, Jan; Wiese, Lothar; Milinkovic, Ana; Hadziosmanovic, Vesna; Clarke, Amanda; Rasmussen, Line D.; Lacombe, Karine; Schommers, Philipp; Staub, Thérèse; et al.
Abstract : Background: Weight gain is becoming increasingly prevalent amongst people with HIV (PWH) receiving contemporary antiretroviral treatment. We investigated BMI changes and clinical impact in a large prospective observational study. Methods: PWH aged ≥18 years were included who started a new antiretroviral (baseline) during 2010–2019 with baseline and ≥1 follow-up BMI assessment available. Rates of clinical outcomes (cardiovascular disease [CVD], malignancies, diabetes mellitus [DM] and all-cause mortality) were analysed using Poisson regression to assess effect of time-updated BMI changes (>1 kg/m 2 decrease, ±1 kg/m 2 stable, >1 kg/m 2 increase), lagged by 1-year to reduce reverse causality. Analyses were adjusted for baseline BMI plus key confounders including antiretroviral exposure. Results: 6721 PWH were included; 72.3% were male, median age 48 years (interquartile range [IQR] 40–55). At baseline, 8.4% were antiretroviral-naive, and 5.0% were underweight, 59.7% healthy weight, 27.5% overweight, and 7.8% were living with obesity. There was an 8.2% increase in proportion of overweight and 4.8% in obesity over the study period (median follow-up 4.4 years [IQR 2.6–6.7]). 100 CVDs, 149 malignancies, 144 DMs, and 257 deaths were observed with incidence rates 4.4, 6.8, 6.6, 10.6 per 1000 person-years of follow-up, respectively. Compared to stable BMI, >1 kg/m 2 increase was associated with increased risk of DM (adjusted incidence rate ratio [IRR]: 1.96, 95% confidence interval [CI]: 1.36–2.80) and >1 kg/m 2 decrease with increased risk of death (adjusted IRR: 2.33, 95% CI: 1.73–3.13). No significant associations were observed between BMI changes and CVD or malignancies. Conclusions: A BMI increase was associated with DM and a decrease associated with death.